2021
DOI: 10.1109/jsait.2021.3053432
|View full text |Cite
|
Sign up to set email alerts
|

On Perfect Privacy

Abstract: The problem of private data disclosure is studied from an information theoretic perspective. Considering a pair of dependent random variables (X, Y ), where X and Y denote the private and useful data, respectively, the following problem is addressed: What is the maximum information that can be revealed about Y , measured by mutual information I(Y ; U ), in which U denotes the revealed data, while disclosing no information about X, captured by the condition of statistical independence, i.e., X ⊥ ⊥ U , and hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In [9], average total variation is used as a privacy measure and a χ 2 -privacy criterion is considered in [5], where an upper bound and a lower bound on the privacy-utility trade-off have been derived. The problem of privacy-utility trade-off considering mutual information both as measures of utility and privacy given the Markov chain X − Y − U is studied in [10]. Under the perfect privacy assumption it is shown that the privacy mechanism design problem can be reduced to a linear program.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In [9], average total variation is used as a privacy measure and a χ 2 -privacy criterion is considered in [5], where an upper bound and a lower bound on the privacy-utility trade-off have been derived. The problem of privacy-utility trade-off considering mutual information both as measures of utility and privacy given the Markov chain X − Y − U is studied in [10]. Under the perfect privacy assumption it is shown that the privacy mechanism design problem can be reduced to a linear program.…”
Section: Introductionmentioning
confidence: 99%
“…This has been extended in [11] considering the privacy utility trade-off with a rate constraint on the disclosed data. Moreover, in [10], it has been shown that information can only be revealed if the kernel (leakage matrix) between useful data and private data is not invertible. In [12], we generalize [10] by relaxing the perfect privacy assumption allowing some small bounded leakage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the problem of private data analysis has attracted much attention from an information-theoretic perspective. A wide variety of privacy measures, for example, mutual information [1][2][3][4][5], measures based on f -divergences [6,7], probability of correctly guessing [8], information privacy [9,10], and log-lift [11,12] are studied that aim to quantify the amount of information leaking about a (private) random variable X by disclosing a related random variable Y . (See [13] for a recent survey on information-theoretic privacy measures.)…”
Section: Introductionmentioning
confidence: 99%